N-(2-hydroxyphenyl)acetamide and its gold nanoparticle conjugation prevent glycerol-induced acute kidney injury by attenuating inflammation and oxidative injury in mice - Siddiqui, Rehan Ahmed; Simjee, Shabana Usman; Kabir, Nurul; Ateeq, Muhammad; Shah, M. Raza; Hussain, Syed Saad (Springer, 2019)
The protective activity of N-(2-hydroxyphenyl)acetamide (NA-2) and NA-2-coated gold nanoparticles (NA-2-AuNPs) in glycerol-treated model of acute kidney injury (AKI) in mice was investigated. NA-2 (50 mg/kg) and NA-2-AuNPs (30 mg/kg) were given to the animals for four days followed by 24-h water deprivation and injection of 50% glycerol (10 ml/kg im). The animals were sacrificed on the next day. Blood and kidneys were collected for biochemical investigations (urea and creatinine), histological studies (hematoxylin and eosin; and periodic acid-Schiff staining), immunohistochemistry (actin and cyclooxygenase-2, Cox-2), and real-time RT-PCR (inducible nitric oxide synthase, iNOS; nuclear factor-κB p50, NFκB; hemeoxygenase-1, HO-1; and kidney injury molecule-1, Kim-1). NA-2 protected renal tubular necrosis and inflammation, though the result of NA-2-AuNPs was better than compound alone and it also exhibited the activity at far less dose. The test compound and its gold nano-formulation decreased the levels of serum urea and creatinine level in the treated animals. Both NA-2 and NA-2-AuNPs also conserved actin cytoskeleton, and lowered COX-2 protein expression. Moreover, the mRNA expressions of iNOS and NFkB p50 were down-regulated, and HO-1 and Kim-1 genes were up-regulated. We conclude that NA-2 and NA-2-AuNPs ameliorates kidney inflammation and injury in glycerol-induced AKI animal model via anti-oxidant and anti-inflammatory mechanisms which make it a suitable candidate for further studies. We believe that these findings will contribute in the understanding of the mechanism of action of paracetamol-like drugs and can be considered for clinical research for the prevention of AKI. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.